ECVET: Piloting between the poles of European requirements and German application practice - Thomann, Birgit [Verfasser]; Eberhardt, Christiane [Verfasser] (My University, 2012)
"This contribution is a strong plea in favor of a training phase abroad, as it provides personal as well as professional motivation. Both is confirmed by the good experience made by executives in enterprises offering their apprentices mobility phases abroad. A view which is also supported by a survey "Hidden mobility in vocational education and training." A vast majority of them underlines that a time spent abroad strengthens the autonomy of their apprentices and see a "boost in their motivation". Admittedly, training phases abroad are still the exception in apprenticeships in Germany, where a stay abroad is predominantly confined to larger companies with more than 500 employees. In recent years progress has been made to create a legal framework which is favorable for training phases abroad, i.e. the amendment of the Vocational Training Act (BBIG). In the last few years there was an array of European instruments fostering transnational mobility. One of them is ECVET, the European Credit Transfer System for Vocational Education and Training. It provides apprentices with the chance of transferring proven learning outcomes to training in their own country and to obtain a credit for their achievements. The results of the pilot projects reveal another important point to be made in future debates ECVET-based mobility elements require favorable general conditions making ECVET approaches available for subsequent use by companies, schools or further educational providers. (BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; Europäisches Leistungspunktesystem; Berufsbildung; Mobilität; Europa